2018
DOI: 10.1523/jneurosci.3484-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing the Roles of Dorsolateral and Anterior PFC in Visual Metacognition

Abstract: Visual metacognition depends on regions within the prefrontal cortex (PFC). Two areas in particular have been implicated repeatedly: the dorsolateral PFC (DLPFC) and the anterior PFC (aPFC). However, it is still unclear what the function of each of these areas is and how they differ from each other. To establish the specific roles of DLPFC and aPFC in metacognition, we used online transcranial magnetic stimulation (TMS) to interfere causally with their functioning during confidence generation. Human subjects f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 52 publications
10
115
2
Order By: Relevance
“…For example, a recent fMRI study found that pgACC tracked all variables necessary for the formation of an internal sense of confidence in a novel psychophysical task that isolates decision confidence from its component parts ( Bang and Fleming, 2018 ). Second, FPl, a region in human prefrontal cortex with no homologue in the monkey brain ( Neubert et al, 2014 ), has consistently been found to track explicit (public) reports of confidence ( Bang and Fleming, 2018 ; Fleming et al, 2012 ; Fleming et al, 2018 ; Gherman and Philiastides, 2018 ; Hilgenstock et al, 2014 ; Shekhar and Rahnev, 2018 ; Yokoyama et al, 2010 ). Of the three ROIs, FPl is of particular interest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent fMRI study found that pgACC tracked all variables necessary for the formation of an internal sense of confidence in a novel psychophysical task that isolates decision confidence from its component parts ( Bang and Fleming, 2018 ). Second, FPl, a region in human prefrontal cortex with no homologue in the monkey brain ( Neubert et al, 2014 ), has consistently been found to track explicit (public) reports of confidence ( Bang and Fleming, 2018 ; Fleming et al, 2012 ; Fleming et al, 2018 ; Gherman and Philiastides, 2018 ; Hilgenstock et al, 2014 ; Shekhar and Rahnev, 2018 ; Yokoyama et al, 2010 ). Of the three ROIs, FPl is of particular interest.…”
Section: Resultsmentioning
confidence: 99%
“…First, recent work has indicated that dorsal anterior cingulate cortex (dACC) ( Fleming et al, 2012 ; Fleming et al, 2018 ) and perigenual anterior cingulate cortex (pgACC) ( Bang and Fleming, 2018 ; De Martino et al, 2013 ; Gherman and Philiastides, 2018 ; Lebreton et al, 2015 ; Wittmann et al, 2016 ) – both located in the medial wall of PFC – support the formation of an internal (private) sense of confidence. Second, a large body of literature has observed activation of lateral PFC, in particular the lateral frontal pole (FPl), in relation to explicit (public) reports of confidence ( Bang and Fleming, 2018 ; De Martino et al, 2013 ; Fleming et al, 2012 ; Fleming et al, 2018 ; Gherman and Philiastides, 2018 ; Hilgenstock et al, 2014 ; Shekhar and Rahnev, 2018 ; Yokoyama et al, 2010 ) – raising the possibility that lateral PFC supports a mapping between private and public confidence. This hypothesis fits with a broader role of lateral PFC in cognitive control functions such as task or set switching ( Badre, 2008 ; Badre and Nee, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present task confidence judgments happened earlier in time than action selection, forcing its explicit computation early onthis could have then been used to inform RL state search. A compelling addition to this argument is that subjects whose decoder was based in PFC, a strong candidate as metacognitive substrate 16,32,58 , also displayed larger effect sizes in confidence-RL correlation measures (Figs. 4a and 5a, b).…”
Section: Discussionmentioning
confidence: 97%
“…It would be of interest to deploy manipulations that alter the correspondence between choice and confidence to a greater degree than what we observed here, while recording simultaneously from sensory and higher order areas. Recent studies in humans point toward several frontal lobe structures involved in generating and reporting the sense of confidence ( Bang and Fleming, 2018 ; Fleming et al, 2015 ; Morales et al, 2018 ; Shekhar and Rahnev, 2018 ). Little is known about where and how such computations occur in the nonhuman primate brain, although the supplementary eye field seems to play a role ( Middlebrooks and Sommer, 2012 ; So and Stuphorn, 2016 ).…”
Section: Discussionmentioning
confidence: 99%